2004
DOI: 10.14507/epaa.v12n72.2004
|View full text |Cite
|
Sign up to set email alerts
|

More than teacher directed or child initiated: Preschool curriculum type, parent involvement, and children's outcomes in the child-parent centers.

Abstract: This study investigated the contributions of curriculum approach and parent involvement to the short- and long-term effects of preschool participation in the Title I Chicago Child-Parent Centers. Data came from the complete cohort of 989 low-income children (93% African American) in the Chicago Longitudinal Study, who attended preschool in the 20 Child-Parent Centers in 1983-1985 and kindergarten in 1985-1986. We found that implementation of an instructional approach rated high by Head Teachers in teacher-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
2
48
0
1
Order By: Relevance
“…One reason for this is that, in the scoring of the ECCOM, child-centered classrooms tend to be operationalized on the assumption that a positive emotional climate prevails, while teacher-directed classrooms tend to be operationalized on the assumption that a less positive emotional climate prevails. Nonetheless, Stipek (Stipek et al, 1995) noted that, although child-centered practices tend to lead to a higher level of motivation among children, teacher-directed practices might contribute positively to children's skill development (see also, Connor et al, 2005;Graue et al, 2004). Finally, the present study was carried out in educational settings within a single country, Finland.…”
Section: Variablesmentioning
confidence: 76%
See 1 more Smart Citation
“…One reason for this is that, in the scoring of the ECCOM, child-centered classrooms tend to be operationalized on the assumption that a positive emotional climate prevails, while teacher-directed classrooms tend to be operationalized on the assumption that a less positive emotional climate prevails. Nonetheless, Stipek (Stipek et al, 1995) noted that, although child-centered practices tend to lead to a higher level of motivation among children, teacher-directed practices might contribute positively to children's skill development (see also, Connor et al, 2005;Graue et al, 2004). Finally, the present study was carried out in educational settings within a single country, Finland.…”
Section: Variablesmentioning
confidence: 76%
“…A few years ago, Graue, Clements, Reynolds, and Niles (2004) found that preschool programs that were high in teacher-directed instruction in specific content areas, while being high in child-centered instruction in other areas of teaching, showed more positive shortand long-term academic and social outcomes in children's development than did practices that emphasized one approach over the other, or that emphasized neither of these two methods. An observation study by Connor et al (2005) supports this view, showing that children whose teachers were ''warmer'' and more responsive in their teaching approach (as in child-centered practices), while also spending more time on academic activities (as in teacher-directed practices), demonstrated stronger vocabulary and basic reading skills at the end of the 1st grade.…”
Section: Variablesmentioning
confidence: 99%
“…Studies that have examined the quality of language and literacy activities in preschool classrooms have shown these to be quite variable, including characteristics of teacher-child conversations and the way in which teachers read books with children during small-and large-group sessions (Dickinson & Sprague, 2002;Girolametto, Hoaken, Weitzman, & van Lieshout, 2000;Graue, Clements, Reynolds, & Niles, 2004;La Paro et al, 2004;McGill-Franzen, Lanford, & Adams, 2002). In general, ratings of preschool instruction are moderate to high when they focus on the general climate of the classroom or teacher sensitivity to students, but are low to mid range when looking at teachers' use of more explicit techniques that may promote children's concept and language development (Girolametto et al, 2000;Girolametto & Weitzman, 2002;La Paro et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Having peers present while reading and talking about mathematics storybooks can be advantageous because children can not only participate as active readers but also use dialogue with each other to understand mathematical vocabulary being addressed in the story [7]. By providing children with guidance and practice on how to use language for reasoning and encouraging storybook talks with peers, children can learn to use language more effectively as a tool for solving problems or discussing new concepts or vocabulary [35,36].…”
Section: Child Development Researchmentioning
confidence: 99%